Efficacy of Itopride in Treatment of Gastroparesis Considering the State of Carbohydrate Metabolism in Patients with Type 2 Diabetes Mellitus - Kostitska I. (Львівський клінічний вісник)
Introduction. Diabetes mellitus (DM) is considered to be one of the most serious problems in internal medicine due to multiple organ lesions and irreversible changes in the functioning of the organism. At present, despite the continuous advancement in medical science pathogenetic mechanisms of the development and progression of gastrointestinal form of autonomic neuropathy, particularly one of its manifestations – diabetic gastroparesis (DG) remains insufficiently studied. Purpose of the study. In the scientific literature there are insufficient data on the clinical efficacy of itopride hydrochloride in patients with impaired motor-evacuation function (MEF) of the stomach. There are no answers to the questions about pathogenetic mechanisms of possible effects of prokinetics on the parameters of glycemic control, the incidence of hypoglycemic events, the progression of gastrointestinal manifestations, etc. Therefore, the objective of the research was to determine therapeutic efficacy of itopride in treatment of gastroparesis considering the state of carbohydrate metabolism in patients with type 2 diabetes mellitus. Materials and research methods. To clarify the relationship between the results of itopride hydrochloride therapy and the dynamics of changes in carbohydrate metabolism were examined 48 patients with type 2 DM. They were divided into two groups. In addition to the standard 6-week course of pathogenetically grounded therapy patients of Group I (n = 24) received itopride hydrochloride at a daily dose of 150 mg (50 mg three times a day 30 min before their main meal). Patients of Group II (the control group) (n = 24) underwent the standard therapy without using medicines affecting MEF of the stomach. The clinical severity of DG was determined using the questionnaire ″Patient Assessment of Gastrointestinal Disorders-Symptom Severity Index″ (PAGI-SYM), which allows the patient to assess the severity of symptoms by himself. According to the survey (D-ABS) the prevalence and intensity of the hypoglycemic episodes were determined. To assess MEF of the stomach all the patients underwent 13C-octanoic acid breath test. Results of the investigation and their discussion. According to the results of additional methods of examination there was a direct correlation between the mean PAGI-SYM scores and the results of 13C-octanoic acid breath test (r = 0.63 ± 0.03, p < 0.001). There was also a strong direct correlation between the state of compensation of carbohydrate metabolism (НbA1C, %) and the degree of slowing of gastrointestinal motility according to the results of 13C-octanoic acid breath test (r = 0.64 ± 0.03, p < 0.001). Thus, the course of DG depends on the effectiveness of glycemic control. Total PAGI-SYM scores indicated the positive effect of treatment which was significantly different in patients of Group I before (14.21 ± 3.28 points – moderate DG) and after the treatment (7.28 ± 0.9 points – mild DG) compared to the control group. The results of 13C-octanoic acid breath test confirmed the effectiveness of a 6-week course of treatment with itopride hydrochloride at a daily dose of 150 mg (50 mg three times a day 30 min before a meal) with recovery of gastrointestinal motility (according to treatment Т ½ – 98.24 ± 3.14 min, in dynamics Т ½ – 68.32 ± 3.55 min; р < 0.05) in patients of Group I. In patients of Group II (the control group) the normalization of MEF of the stomach after the course of treatment was not observed (before treatment Т ½ – 97.23 ± 2.61 min, after treatment Т ½ – 92.12 ± 0.16 min; р >0.05). Conclusions. The effectiveness of using itopride hydrochloride at a daily dose of 150 mg has been proven. It has been established that it contributes to normalizing MEF of the stomach in patients with type 2 DM and signs of DG as well as achieving better compensation of carbohydrate metabolism of both prandial and postprandial glucose levels. The possibility of using prokinetic agents to prevent the labile course of DM should be taken into consideration.